Rapid acclimation of the cortisol stress response in adult turquoise killifish Nothobranchius furzeri. (August 2019) - Henderson, Dallas W; Small, Brian C
The turquoise killifish Nothobranchius furzeri is an increasingly popular model species for comparative vertebrate research, and the basic physiology including responses to stressful stimuli are of primary interest. We exposed adult killifish to a single or repeated periods of acute confinement followed by analysis of tissue cortisol and plasma cortisol concentrations. Individuals were also sampled for messenger RNA (mRNA) expression of corticotropin-releasing hormone ( CRH ), mineralocorticoid receptor ( MR ), and glucocorticoid receptor ( GR ) in the brain to examine the effects of repeated stress events on constitutive expression of these important stress axis components. Following a single 30-minute confinement stress, male plasma cortisol significantly differed from baseline ( p = 0.04). Both male and female whole-body cortisol were significantly increased ( p = 0.004 and p = 0.04, respectively) at 15 and 30 minutes poststress. Despite obvious dimorphic behavior and morphology, cortisol concentrations did not differ between the sexes. Exposure to daily repeated confinement for one week altered the cortisol response in both sexes. Time 0, 15, and 60 minutes poststress cortisol concentrations were depressed in repeatedly stressed males ( p ≤ 0.05), and times 0, 30 and 120 minutes poststress cortisol concentrations were depressed in repeatedly stressed females ( p ≤ 0.05). Constitutive expression of CRH, MR, and GR mRNA in the brain following one week of repeated stress events did not differ among treatments or sexes. This study introduces the first description of hypothalamic-pituitary-interrenal axis activity in this important model species. Reduced cortisol production in repeatedly stressed adult killifish suggests acclimation to repeated stressors. Furthermore, acclimation was rapid, and plasma cortisol concentrations altered significantly in as little as one week.